The Study of Release of Chlorhexidine from Preparations with Modified Thermosensitive Poly-N-isopropylacrylamide Microspheres - Witold Musial; Bojana Voncina; Janusz Pluta; Vanja Kokol (The Scientific World Journal)
The aim of this study was to investigate and compare the release rates of chlorhexidine (CX) base entrapped in the polymeric beads of modified poly-N-isopropylacrylamides (pNIPAMs) at temperatures below and over the volume phase transition temperature (VPTT) of synthesized polymers: pNIPAM-A with terminal anionic groups resulting from potassium persulfate initiator, pNIPAM-B with cationic amidine terminal groups, and pNIPAM-C comprising anionic terminals, but with increased hydrophobicity maintained by the N-tert-butyl functional groups. The preparations, assessed in vitro below the VPTT, release an initial burst of CX at different time periods between 120 and 240 min, followed by a period of 24 h, when the rate of release remains approximately constant, approaching the zero-order kinetics; the release rates for the polymers beads are as follows: pNIPAM-C>pNIPAM-B>pNIPAM-A. The pattern of release rates at temperature over the VPTT is as follows: pNIPAM-C>pNIPAM-A>pNIPAM-B. In the presence of pNIPAM-C, the duration between the start of the release and the attained minimal inhibitory concentration (MIC) for most of the microbes, in conditions over the VPTT, increased from 60 to 90 min. The release prolongation could be ascribed to some interactions between the practically insoluble CX particle and the hydrophobic functional groups of the polymer.